2005
DOI: 10.1002/j.0022-0337.2005.69.12.tb04031.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Competence of Graduates of Community‐Based and Traditional Curricula

Abstract: As community-based dental education programs proliferate, so do concerns about the quality of education at extramural sites. While there have been some comparisons of the effects of community-based programs on attitudes and perceptions of competency, there is virtually no information about whether such programs can train students to carry out standard dental procedures as well as if they were prepared in the dental school proper. To address this gap in our knowledge about the educational outcomes of community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 8 publications
(3 reference statements)
2
26
0
1
Order By: Relevance
“…Prior studies have shown how CBDE has positively impacted students' clinical performance, improved their self-perceived communications and interpersonal skills, and contributed to their willingness to provide care in the future for populations that are underserved. 17,18,28,29 However, to the best of our knowledge, there has not been previous documentation of didactic content that is used to augment these community-based experiences. With our indings, one could speculate that the respondents deemed it important for students to be aware of the structural factors impacting underserved and rural communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown how CBDE has positively impacted students' clinical performance, improved their self-perceived communications and interpersonal skills, and contributed to their willingness to provide care in the future for populations that are underserved. 17,18,28,29 However, to the best of our knowledge, there has not been previous documentation of didactic content that is used to augment these community-based experiences. With our indings, one could speculate that the respondents deemed it important for students to be aware of the structural factors impacting underserved and rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…15 As many of these rotations train students to provide care for multiple patients in a clinical session, CBDE also helps dental students gain experiences that increase their clinical productivity and eiciency. 11,[16][17][18][19][20][21] However, there is limited evidence of the extent to which these rotations augment clinical training with learning about the social, political, professional, and economic factors that shape the attitudes and behaviors of patients and health care providers.…”
mentioning
confidence: 99%
“…Many attending the mobile clinic are often later successfully transferred to the fixed site clinic. 10 It may be that student input is more beneficial within the mobile dental service where more of the homeless patients are likely to be at the start of their treatment. Provision of oral health advice by students may additionally improve patient confidence in accessing mainstream services.…”
Section: Discussionmentioning
confidence: 99%
“…8 Clinically, students at the University of New Jersey who had spent their final years' clinical time within communitybased placements had more experience of restorative treatment and felt more clinically prepared than those who spent it within the dental school. 10 In 2011, the Department of Health commissioned London Pathways to set out a Homeless health standard 2 providing a national strategy for the healthcare of homeless people. This includes specific recommendations for the 'education and involvement in undergraduate and postgraduate training of… dental students' in the 'promotion and encouragement of accessible provision of dental care'.…”
Section: Introductionmentioning
confidence: 99%
“…internationally (19)(20)(21); as such it is recognised as being able to give dental students an invaluable experience and expose them to a wide range of patients. Previous documentation from the GDC recommended a period of time in a primary care setting to extend the clinical environment that students could experience (22).…”
Section: Introductionmentioning
confidence: 99%